Mucoadhesive chitosan hydrogels as rectal drug delivery vessels to treat ulcerative colitis. (15th January 2017) - Xu, Jinke; Tam, Mifong; Samaei, Sepideh; Lerouge, Sophie; Barralet, Jake; Stevenson, Mary M.; Cerruti, Marta
Graphical abstract: Abstract: Mucoadhesive drug delivery systems stick to mucosal tissues and prolong the local retention time of drugs. Since the colon is covered by a mucosal layer, mucoadhesive rectal formulations may improve treatment of such diseases as hypertension or colon cancer. Ulcerative colitis (UC) is an inflammatory bowel disease characterized by chronic inflammation of the colonic mucosa. It is commonly treated with sulfasalazine (SSZ), which is metabolized by the intestinal flora into the therapeutic 5-aminosalicylic acid (5-ASA) and a toxic by-product sulfapyridine (SP). SSZ can be administered orally or rectally. The latter route avoids unintended absorption of the drug or its degradation products in the upper gastrointestinal tract, but often fails due to limited retention time. Here, we propose a mucoadhesive hydrogel to improve the efficacy of rectal SSZ administration. The gel is made of catechol modified-chitosan (Cat-CS) crosslinked by genipin. After loading the gel with SSZ, we evaluated its efficacy in a mouse model of UC. Compared to oral SSZ treatment, rectal SSZ/Cat-CS delivery was more therapeutic, showed equivalent histological scores, and induced a lower plasma concentration of the potentially toxic SP by-product. These results show SSZ/Cat-CS rectal hydrogels are more effective and safer formulations for UC treatment than oral SSZ. Statement of Significance: Ulcerative colitis affects the colon by causing chronic inflammation on the mucosa. One of the most common drugs to treat mild to moderate UC is sulfasalazine, which can be administrated both orally and rectally. Rectal formulations are preferable, since their therapeutic effect happens topically, and they prevent side effects related to absorption of the drug in the small intestine. However, the efficacy of rectal sulfasalazine formulations is decreased by their limited colon residence time. Here we propose a chitosan-catechol mucoadhesive gel that allows delivering sulfasalazine more effectively and safely than oral administration. Our results bring new insights into the field of mussel-inspired catechol hydrogels, showing their potential as drug delivery systems to treat a widespread disease such as ulcerative colitis.